Using Static Magnetic Field to Overcome Salt Stress in Maize Seeds - Tamara Sabah Hadi; Mohammad Salman Kareem (Academia Open, 2025)
General Background: Salinity stress is a major environmental factor limiting crop productivity worldwide, particularly affecting early growth and germination stages in maize (Zea mays L.), a crop vital for food security and industry. Specific Background: Recent advances in agricultural biophysics have highlighted magnetic field treatment as a safe, cost-effective method to stimulate plant physiological responses and improve stress tolerance. However, its mechanisms and efficacy under salinity conditions remain insufficiently explored. Knowledge Gap: Few studies have systematically assessed the effect of static magnetic fields on maize germination and seedling vigor under salt-induced osmotic stress. Aims: This study aimed to evaluate the impact of static magnetic field pretreatment on maize seed germination, seedling growth, and proline accumulation under varying salinity levels. Results: Exposure to 100 mT for two hours significantly enhanced germination percentage, seedling vigor, proline content, and field emergence compared to untreated controls, particularly under 2000 mg/L NaCl stress. Novelty: The findings demonstrate that static magnetic fields can mitigate the negative effects of salt stress by promoting physiological resilience without chemical intervention. Implications: This technique provides an eco-friendly strategy to improve maize establishment and productivity in saline-prone agricultural systems.Highlight : Exposure of maize seeds to static magnetic field enhanced germinability under salinity stress conditions. Magnetic pretreatment improved seedling vigor, proline content, and field emergence. The 100 mT for two hours treatment showed the best performance in mitigating salt stress. Keywords : Maize, Magnetic Field, Salinity, Germinability, Field Emergence